The Influence of Servant Leadership on Employee Satisfaction at Pangeran Beach Hotel Padang - Dimas Rasyihan; Arif Adrian (Journal of Multidimensional Management, 2025)
This study investigates the influence of servant leadership on employee satisfaction within the hospitality industry by examining key leadership dimensions such as compassion, empowerment, vision, humility, and trust. Using a quantitative approach, data were collected from 88 respondents through structured questionnaires and analyzed with SPSS version 26. The analysis included descriptive statistics, validity and reliability testing, classical assumption testing, and hypothesis testing through regression analysis. Results show that servant leadership has a significant positive effect on employee satisfaction, with all leadership indicators demonstrating strong contributions to fostering a supportive and motivating work environment. Employee satisfaction was found to be in the very good category, reflecting positive perceptions toward job involvement, morale, discipline, and performance. These findings highlight that servant leadership not only enhances employee satisfaction but also supports organizational effectiveness by reducing turnover intention and improving overall service quality. The study provides valuable managerial implications for hospitality organizations, emphasizing the need for leaders to adopt servant leadership practices as a strategic approach to strengthen employee engagement and satisfaction.